Analisis Strategi Penanganan Peredaran Narkoba di Rumah Tahanan Negara Kelas II B Banyumas - Alfin Azka Fauzi; Arisman Arisman (Mahesa Research Center, 2021)
This study aims to find out how to handle drug trafficking strategy in Banyumas Class II B State Prison. The type of research conducted is a qualitative type of research and uses quantitative data collection method used to analyze environmental factors with SWOT method, research sample is 19 officers with sample determination based on purposive sampling technique. The results of this study showed that the strategy of handling drug trafficking shows an aggressive strategy located in quadrant I so that banyumas Class II B State Prison should be able to utilize momentum in order to handle drug trafficking and also be able to control the movement of existing drugs.